Հայ–վրացական հարաբերությունները XVIII դարի II կեսին և հայ քաղաքական միտքը - Չոբանյան, Պավել («Զանգակ - 97»)
In the programmes directed to the liberation of Armenia during the second half of the XVIII Century the Armenian political idea had assigned an important role to Georgia. In spite of its protectionist policy towards the Armenian population, Georgia was unable to assist them in the restoration of the Armenian statehood. This was the case when Simeon Yerevantsi was inclined to act on his own for uniting Armenians, at the same time looking for Russian assistance. A part of the Armenian meliks holds the policy of collaboration with Iran, which culminated in failure.
Keywords: Պատմություն; Քաղաքականություն